DAMPAK KEBERADAAN MINIMARKET ALFAMART TERHADAP PENDAPATAN USAHA MIKRO KECIL DAN MENENGAH (UMKM) KOTA WATAMPONE - Astiana S; Syahrir Pawerangi; Andi Ferawati (JURNAL ILMIAH EKONOMI, MANAJEMEN, BISNIS DAN AKUNTANSI, 2024)
The Impact of the Existence of the Alfamart Minimarket on the Income of Micro, Small and Medium Enterprises (MSMEs). Thesis of the Accounting Study Program at the College of Economics (STIE YAPI BONE) The aim of the research is to collect information regarding the impact of the existence of the Alfamart minimarket on the income of small and medium enterprises (UMKM). In this research, in general the people in Watampone City fulfill their livelihood needs by doing business or entrepreneurship, trading and some also work as laborers, private employees and others. Because the presence of a minimarket around their business will of course have an impact on their income. This research was conducted based on field research and used qualitative descriptive methods, namely interviews with 15 (fifteen) wholesalers and retailers, interviews were conducted comfortably and simply, easy to use, the questions asked were not interrogative but only for certain purposes. The aim is to obtain the desired data to complete the research article. The results of the research show that there has been a change in the income of traders who were initially able to earn profits of up to 10 million per day, but after the emergence of the Alfamart Minimarket, their income decreased or decreased. The government's lack of concern for the sustainability of traders' businesses and the ease of granting permits to build convenience stores adds to traders' concerns.